1985
DOI: 10.1111/j.1399-6576.1985.tb02244.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Dopamine Suppress Stress‐Induced Intestinal and Renal Vasoconstriction?

Abstract: Dopamine interference with intestinal and renal sympathetic reflex vasoconstrictor responses was studied in cats anaesthetized with diazepam, fentanyl and nitrous oxide. Vasoconstriction was induced by electric stimulation of the hypothalamic defence-alarm area and by stimulation of somatic and visceral afferents. In addition, intestinal vasoconstriction was elicited by direct stimulation of postganglionic sympathetic efferent nerves. In the intestine, dopamine administration (7.5 microgram X kg-1 X min-1) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 19 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…At low doses (2.5 μg/kg/min) dopamine stimulates canine dopaminergic receptors causing vasodilation in the renal and mesenteric vasculature. In contrast, low‐dose dopamine infusion may not dilate the feline renal vasculature 89 . Higher doses (5–10 μg/kg/min) stimulate β 1 and α 1 adrenoreceptors resulting in increased myocardial contractility and vasoconstriction.…”
Section: Recommendationsmentioning
confidence: 99%
“…At low doses (2.5 μg/kg/min) dopamine stimulates canine dopaminergic receptors causing vasodilation in the renal and mesenteric vasculature. In contrast, low‐dose dopamine infusion may not dilate the feline renal vasculature 89 . Higher doses (5–10 μg/kg/min) stimulate β 1 and α 1 adrenoreceptors resulting in increased myocardial contractility and vasoconstriction.…”
Section: Recommendationsmentioning
confidence: 99%
“…For several years, it was believed that cats did not have renal dopamine receptors as low-dose dopamine administration to healthy cats and direct DA1 activation with fenoldopam did not result in an increase in urine production. 99,100 It was concluded that any diuretic effect was probably due to pressure diuresis caused by a-adrenergic activation. 100 Increased local metabolism of dopamine might be a reason for the missing diuretic effect of low-dose dopamine therapy in cats.…”
Section: Current Published Human Researchmentioning
confidence: 99%
“…Stress . At least a substantial component of stress or behavioral hyperthermia is a true fever; 61 as gut blood flow is much lower in the stressed animal 62,63 (and there are presumably also other changes, such as elevated catecholamines, which would diminish the gut endotoxin barrier), there is a clear opportunity for involvement of gut endotoxins in the development of fever in the stressed animal.…”
Section: E Other Thermoregulatory Responses That Could Involve Gut Ementioning
confidence: 99%
“…59,60 Stress . At least a substantial component of stress or behavioral hyperthermia is a true fever; 61 as gut blood flow is much lower in the stressed animal 62,63 (and there are presumably also other changes, such as elevated catecholamines, which would diminish the gut endotoxin barrier), there is a clear opportunity for involvement of gut endotoxins in the development of fever in the stressed animal. Mechanisms underlying the second phase of the biphasic body temperature response often seen in fever have been extensively studied but remain unclear. 64 In view of the present discussion, it is not difficult to imagine that gut endotoxins are involved, gaining access to plasma because of the decreased gastrointestinal blood flow that occurs with the initial development of fever.…”
Section: E Other Thermoregulatory Responses That Could Involve Gut En...mentioning
confidence: 99%